Features of the brainstem and tentorial foramen relationship and their practical value - O. V. Redyakina (Kazimierz Wielki University, 2016)
Objective. Establish the morphological features and practical significance of the tentorial-stem relationship from the position of individual anatomical variability. Methods: head morphometry, macro and microscopic examination of the brainstem, morphometry of the brainstem and its departments, tentorial aperture morphometry, foramen magnum craniometry, manufacture of corrosion molds of the posterior cranial fossa, statistical processing of the results, computer-graphic modeling of the brainstem and surrounding formations. Results.  In the course of the study, the features of the individual variability of the tentorial foramen form were established, namely: shortened-expanded and oval-convex forms were defined in brachycephalic; in dolichocephalic - oblong-narrowed and elongated-conical. At the same time, a number of existing sizes and forms of the tentorial-stem spaces were noted. Among them, four main ones are described: front, side (right and left) and rear. They have individual characteristics. Thus, in the brachycephalic we define lateral holes, due to the convexity of the tentorial margins. In dolichocephalic - front and back gaps, depending on the characteristics of their elongations. The obtained data are of great importance for the craniotopographic justification of the tentorial-stem wedges, which are formed with tumors which located here. In our opinion, tumors have the greatest possibility of passage through the left or right lateral intervals in people with a brachymorph form of the head, and through the anterior and posterior intervals - in people with meso- and dolichomorph forms of the head.